PENGARUH PENGGUNAAN MEDIA GOOGLE EARTH DAN PETA TERHADAP PENINGKATAN HASIL BELAJAR GEOGRAFI - Else Ervina; Buchori Asyik; Dedy Miswar (JPG (Jurnal Penelitian Geografi), 2013)
The aims of his research were: (1) to describe the influence in the use of google earth media to increase the result of students’ learning outcomes of geography for the material of Southeast Asia at SMA 14 Bandar Lampung. (2) to find out the difference of students’ learning outocomes for the material of Southeast Asia nation using google earth learning media by using map at XI IPS class of SMAN 14 Bandar Lampung. The population of this research is the students of XI IPS Negeri 14 Bandar Lampung who were 332 students. The sample of the research was carried out by cluster sampling techniques so the researcher got XI IPS1 class (experimental class) and XI IPS II Class (control class) as samples. The researcher used Independent T-test as the technique of data analysis for the results of students’ learning outcomes. The result of the research indicated that for the first hypothesis, the significance value was 0.183 so it can be inferred that significance value was 0.05, then Ho was accepted. For the second hypothesis, it was 0.001 0.05, then Ho was denied so it can be concluded that there is a difference of students’ learning outcomes whose learning used google earth media the first meeting at SMAN 14 Bandar Lampung which means the stusents who have improvement in the second meeting and student learning outcomes in the used os google earth media are higher that in the use of map both at the first and second meeting. Keywords: student learning outcomes, the use of google earth media, google earth